Comparing System Dynamics Simulation and Case-Based Learning for Students’ Understanding of Freight Management - Noneng Nurjanah; Nanang Rosidin (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Freight management education is still largely dominated by static instructional approaches that provide limited opportunities for students to understand the dynamic nature of logistics systems. As a result, students often struggle to comprehend causal relationships, feedback mechanisms, and the effects of delays on system performance. This study aims to examine the effectiveness of system dynamics-based learning in improving students’ understanding of freight management systems compared with conventional case-based instruction while controlling for prior knowledge. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design involving 32 undergraduate students. The data were analyzed using Analysis of Covariance (ANCOVA). The ANCOVA model explained 78.4% of the variance in post-test scores (R² = 0.784), with prior knowledge having a positive and significant effect on post-test performance. Students who participated in the system dynamics simulation also achieved higher post-test scores than those in the control group, although the treatment effect was only marginally significant. These findings suggest that system dynamics simulation has the potential to strengthen students’ understanding of dynamic freight management concepts and promote systems thinking. Integrating SD simulation into logistics education can therefore complement conventional teaching approaches and better prepare students to address the complexity of real-world logistics systems.